A Study on Difficulties and Solutions in Listening Comprehension Among EFL Learners - A'R, Daffa Wahyu; Muzammil, Lasim; Purnawati, Maria (Journal of English Language and Education, 2025)
Listening was acknowledged as a foundational skill for EFL students’ language acquisition. Despite the importance of listening comprehension, many EFL students still struggled to comprehend effectively due to various difficulties. This research investigated the listening comprehension difficulties and additional solutions experienced by twelfth-grade EFL students and teachers from SMA Nasional Malang. This study used a mixed-method sequential explanatory design, with the population consisted of 31 twelfth-grade students and two English teachers who taught them. The findings indicated five significant difficulties that emerged such as unfamiliar accents, unfamiliar words, distraction from comprehension gaps, distractions, and fast speech. Several solutions were also proposed to minimize these difficulties. Teachers and students emphasized additional solutions such as authentic media, subtitle support, vocabulary enrichment, authentic exposure, gradual and interactive listening activities, self-regulated learning, students’ positive mindset and motivation building, learning style integration, and Project-Based Learning (PJBL).